Optimization of Biodiesel Synthesis from Waste Cooking Oil By Transesterification Process in A Microwave - Ika Yuliana Wati; Rosavinda Nurfauziah; Susilowati; Ika Nawang Puspitawati; Diyah Suci Perwitasari; Suprihatin; Adityas Agung Ramandani (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2025)
The rising energy demand in Indonesia is driving the development of biodiesel as a sustainable, renewable fuel. Waste cooking oil has the potential as a biodiesel feedstock due to its abundant availability and relatively low cost. Biodiesel is generally produced via transesterification, but conventional heating methods have limitations, such as long reaction times and high energy consumption. Therefore, microwave-based heating is used as an alternative to improve process efficiency through rapid, even heating. This research aims to' optimize biodiesel synthesis from used cooking oil using a microwave-assisted transesterification process with the Response Surface Methodology (RSM) and Analysis of Variance (ANOVA) approaches. The process variables studied include catalyst' concentration (1', 2, 3, 4, and' 5%w/w) and' reaction time (2, 4, 6, 8, and 10 minutes), with biodiesel yield as the main response. A mathematical model was developed using an appropriate experimental design and statistically validated using ANOVA to assess the model's significance and the effects of interactions between variables. The research results showed the highest biodiesel yield at 4% catalyst with a reaction time of 6 minutes. The RSM method, validated by ANOVA, was effective in determining optimum operating conditions and increasing biodiesel yield. This approach has the potential to be applied as a highly effective and sustainable method for biodiesel production from used cooking oil. Contribution to Sustainable Development Goals (SDGs):SDG 7: Affordable and Clean EnergySDG 12: Responsible Consumption and ProductionSDG 13: Climate ActionSDG 15: Life on' Land